A problem shared is a problem halved? Risky tax avoidance decisions and intra-group payoff conflict - Eva Kristina Matthaei; Dirk Kiesewetter (Arbeitskreis Quantitative Steuerlehre (arqus), 2020)
This paper investigates the dynamics of group decisions regarding risky tax avoidance strategies using a laboratory experiment. To identify the causes of risk taking by groups, we compare individual to group decisions in three scenarios. The first scenario allocates payoffs from group decisions equally to all members of a group. The second and third scenario introduce intra-group payoff conflict as a new influential factor in group dynamics. Hereby, we separate intra-group payoff conflicts in the distribution of costs and profits. This manipulation allows us to disentangle group discussion effects resulting from the competing theories of polarization and diversification of opinions. Our overall findings support a predominant diversification of opinions effect. When group members share all payoffs equally, this effect overcomes polarization in 100% of the cases where outstanding individuals are risk averse, while group polarization appears to be more likely towards outstanding risk loving subjects. Intra-group payoff conflict shifts these likelihoods, supporting the importance of rational arguments in group polarization. Consequently, our experimental results support a strong increase in the level of average tax avoidance following group decisions in case of all or negative outcomes being shared equally by group members. Intra-group payoff in the distribution of costs, however, removes this difference and shifts, both individual and group preferences, towards safety.
Keywords: 330; group; tax avoidance; risk; intra-group payoff conflict; polarization; diversification of opinions; Steuervermeidung; Entscheidung unter Risiko; Gruppenentscheidung; Experiment; Theorie